Exploring Perceptions of Indonesian Business and Administration Students on Their English Academic Writing Skill in ESP - Ginting, Rita Seroja; Dalimunte, Ahmad Amin (Language Circle: Journal of Language and Literature, 2023)
Writing academic papers is challenging for students majoring non-English programs in higher education. This is because they must both understand academic writing conventions and English writing rules at the same time. This case study explores further perceptions of university students of Business and Administration regarding their academic writing skill. 20 students were selected by purposive sampling technique and were administered an online questionnaire to collect the data. Afterwards, three volunteer students joined in-depth interview to find out more information from the online questionnaire. The data were then analyzed by two techniques including frequency count for the quantitative data and qualitative analysis by employing thematic analysis for the qualitative data. The results discovered that students' perceptions of their academic ESP written competence in Business English were positive. Students are aware of both their own and the ESP writing requirements. However, these positive attitudes have not yet been fulfilled with appropriate writing lessons. Therefore, it is important for further research to conduct a study regarding the ESP writing lesson that works best for the students.